2021
DOI: 10.5604/01.3001.0014.8746
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout Among the Managers of Polish Nonprofit, for-Profit and Public Organizations

Abstract: The issue of job burnout has been paid a great deal of attention over the years, due to entailing several negative consequences for employees’ well-being, health, organizational behaviour. Job burnout may affect employees of any category, being rooted not only in personality and interpersonal factors but also in organizational factors. The purpose of the article is to answer the following research question: Are there any differences between Polish nonprofit, for-profit and public organizations regarding manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…According to Deng et al (2021), employees in nonprofits are marked by high burnout rates. This was also confirmed by comparative studies carried out among managers of nonprofit, for-profit and public organisations, in which the highest rate of professional burnout was reported among NPOs leaders (Seiler and Bortnowska, 2021).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…According to Deng et al (2021), employees in nonprofits are marked by high burnout rates. This was also confirmed by comparative studies carried out among managers of nonprofit, for-profit and public organisations, in which the highest rate of professional burnout was reported among NPOs leaders (Seiler and Bortnowska, 2021).…”
Section: Introductionsupporting
confidence: 57%
“…Craiovan, 2015;Pomerantz, 1991;Romina, 2016). Moreover, cross-sector research by Seiler and Bortnowska (2021) demonstrated that NPO managers are marked by the highest rate of professional burnout compared to the representatives of the managerial staff employed in the other types of entities.…”
Section: Job Burnoutmentioning
confidence: 99%
“…It can, therefore, improve the image of NPOs and foster fundraising from different donors. There is a high turnover among the volunteers who make up project teams, so motivating them and keeping them engaged throughout the project is a major challenge (Seiler, Bortnowska, 2020). GPM can support project teams to acquire ecological knowledge and develop the responsible use of resources, while at the same time providing ample opportunities to develop competencies and care for their needs, as well as the needs of potential service recipients (rather than the needs of the organisation) -taking into account their scale and hierarchy (Marciszewska, 2014).…”
Section: Introductionmentioning
confidence: 99%